Inovação em cuidados à saúde: um estudo da produção dos equipamentos de diagnóstico por imagem - Pedrosa, Rodolfo Batista (2019)
This dissertation focus on analyzing the industry of Medical imaging equipments and highlighting the importance of technological innovation in those equipments, whether in its economical aspects, inside the Industrial-Economic Health Complex, whether social aspects, associated to its introduction and diffusion in the healthcare system. In order to that, this dissertation seeks to understand how the innovations are generated in the productive sector of mechanical basis, electronics and materials and, specially, imaging diagnostic equipments and its technological path; the importance of an innovative environment able to provide help to national industry; governamental incentive policies after 2003; the distribution of such equipments in assistance network which are available to the population; and, also, the commercial flow between Brazil and the rest of the world. In order to that, has been made a bibliographic review about thematics involved in this research using scientific papers and qualitative and quantitative analysis of oficial industry data. Quest Orbit has been used to support families patents analysis around the world. It was observed that despite all the governamental incentive polices, it has not been able to significant reduces importation amount and that nacional industry has not a high level innovation ratio in this studied sector.